2005
DOI: 10.1075/ni.15.1.06mel
|View full text |Cite
|
Sign up to set email alerts
|

Variations in maternal narrative styles during book reading interactions

Abstract: The present study examined the narrative styles of Spanish-speaking Peruvian and English-speaking U.S. American, college-educated mothers as they shared a wordless book with their three-year old children. Results show two distinct book reading narrative styles: Storytellers, who act as the sole narrator of an engaging story with minimal child participation, and storybuilders, who co-construct the story with their young children. The two maternal styles are discussed in relation to possible differences in conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 31 publications
7
83
0
3
Order By: Relevance
“…Our findings further suggested that mothers' book‐sharing styles are associated with individual and ethnic variations in children's storytelling styles. Our findings highlighted the role of questions – characteristic of a dialogic style – for children's narrative development (Cristofaro & Tamis‐LeMonda, ; Kang et al, ; Melzi & Caspe, ; Reese & Newcombe, ). At the individual level, mothers' questions were associated with children's narrative contributions during book‐sharing.…”
Section: Discussionsupporting
confidence: 56%
“…Our findings further suggested that mothers' book‐sharing styles are associated with individual and ethnic variations in children's storytelling styles. Our findings highlighted the role of questions – characteristic of a dialogic style – for children's narrative development (Cristofaro & Tamis‐LeMonda, ; Kang et al, ; Melzi & Caspe, ; Reese & Newcombe, ). At the individual level, mothers' questions were associated with children's narrative contributions during book‐sharing.…”
Section: Discussionsupporting
confidence: 56%
“…We need to expand this line of research by including and emphasizing other factors, such as examining the effects of mothers' choices for reading to their children on the children's subsequent reading habits (e.g., Reynolds and Evans 2009). Similar maternal narrative styles are, in fact, observed during other narrative contexts, such as picture book reading interactions (Melzi and Caspe 2005). We should include the interaction between mother and child when the mother reads to her child, because shared book reading is similar to the dialogic mode of narrative telling, in which, as we have seen, interaction proceeds through a question-answer format (e.g., mothers try to extend topics by providing requests for actions, descriptions, and evaluations, to which children respond).…”
Section: Future Researchsupporting
confidence: 57%
“…Cultural aspects of parents' narrative style can also be respected. Parents from different cultures and different SES levels have different approaches to narratives (Hoff-Ginsberg, 1991;Melzi, 2000;Melzi & Caspe, 2005). SHELLS does not require a specific narrative approach but allows the parent to guide the storytelling process, respecting his or her cultural strength.…”
Section: Methodsmentioning
confidence: 98%